Evaluation of damage caused by some species of rodents on sugar cane and sugar beet - Abdel-Aziz, N.; Al-Gendy, A. T. R.; Baghdadi, S. A. S.; Elrawy, A. A. A. (Journal of Phytopathology and Disease Management, 2017)
The damage caused by the nile grass rat, Arvicanthis niloticus (Desmarest) and the white bellied rat, Rattus rattus frugivorous (Rafinesque) on sugar cane variety G.T. 54-9 was evaluated in three areas (Al-Hasany ; Al shek wefy and Ber El-Nos) at Qena Governorate during 2014 and 2015. The highest infestation was recorded in Ber Elnos area while Al-Hasany showed the lowest infestation during the two seasons. The percentage of infestation in sugar cane was higher in the first season than that in the second. The damage caused by A. niloticus, R. r. frugivorous and Rattus rattus alexandrines (Geoffray) on sugar beet was high in Assiut district during two cultivation seasons.. The losses in sugar beet weight was due to the damage caused by the three rodent species was (10.7, 10 and 6.7%) and (6.7, 6 and 4%) for the two seasons. The damage was concentrated at the upper part of the root.